Ambiguous Bodies: The Role of Displayed Arousal in Emotion [Mis]Perception. - Reynolds, R. M.; Novotny, E.; Lee, J.; Roth, D.; Bente, G. (Journal of Nonverbal Behavior, 2019)
Emotions of other people cannot be experienced directly but are often inferred from a variety of verbal and nonverbal information, including expressive body movement (EBM). Inferring emotional states is critical in social interaction, and questions remain about the factors contributing to ambiguity of EBM. In addressing this issue, researchers have looked to the link between displayed arousal, or the intensity of the emotional expression, and the potency of a nonverbal signal to convey emotional content such as valence or category. This study reports experimental results that address limitations of prior research regarding the ambiguity of EBM. Using motion-capture technology that permits isolation of expressive cues, the results suggest that for displays of anger and happiness (a) the ambiguity of the emotional valence and category increases as a linear function of the displayed arousal, and (b) observers show a negative response bias and greater sensitivity to negative cues. Implications of these findings for research on emotion perception are discussed.